1998
DOI: 10.1038/bjc.1998.77
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of age on survival of 341 patients with multiple myeloma treated with conventional chemotherapy: updated results of the MM87 prospective randomized protocol

Abstract: Summary Age could influence the prognosis of multiple myeloma patients treated with conventional chemotherapy. Between January 1987 and March 1990, 341 consecutive previously untreated patients with multiple myeloma received chemotherapy within the prospective, multicentre, randomized Protocol MM87. Survival was evaluated in patients aged > or < 66 years (the median age for the whole series) and in a subgroup of patients aged < 55 years. These groups were similar for main clinical characteristics, including re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
2
19
0
2
Order By: Relevance
“…Indeed, there are conflicting reports about the impact of patient age on prognosis in newly diagnosed multiple myeloma. Some studies have reported that patients with advanced age have an inferior survival compared with younger patients, [29][30][31][32][33] whereas others have reported no effect once other prognostic variables such as C-reactive protein and ␤ 2 M levels are considered. [34][35][36][37] Advanced age does not appear to be predictive of inferior outcome following high-dose chemotherapy and autologous stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are conflicting reports about the impact of patient age on prognosis in newly diagnosed multiple myeloma. Some studies have reported that patients with advanced age have an inferior survival compared with younger patients, [29][30][31][32][33] whereas others have reported no effect once other prognostic variables such as C-reactive protein and ␤ 2 M levels are considered. [34][35][36][37] Advanced age does not appear to be predictive of inferior outcome following high-dose chemotherapy and autologous stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…34 However, our data confirm the results of several other studies showing that achieving CR has an important influence on PFS and that this subset of patients may derive the greatest benefit from the procedure. 10,35 Advanced age has been shown to be a poor prognostic factor in several trials using conventional chemotherapy [5][6][7] or ASCT. 26,27 An Italian study of 290 patients showed that age emerged as an important prognostic factor at a cutoff value of 55 years, 26 while other studies using a cutoff value of 65 years or even 70 years have suggested that age is not an exclusion criterion for ASCT programmes.…”
Section: Asct In Multiple Myeloma E Terpos Et Almentioning
confidence: 99%
“…1 The outcome for MM patients after chemotherapy has not changed dramatically since the introduction of melphalan and prednisone, although a large number of different chemotherapy combinations have been used. [2][3][4] Advanced age is a poor prognostic factor in several trials using conventional chemotherapy [5][6][7] even if the biological and clinical features in elderly MM patients are identical to those of younger patients. 8,9 In the absence of any significant improvement after various conventional chemotherapies, high-dose therapy with autologous stem cell transplantation (ASCT) has been extensively used in the last decade leading to higher complete remission (CR) rate with longer progression-free (PFS) and overall survivals (OS).…”
mentioning
confidence: 99%
“…2 Advanced age is a poor prognostic factor in several trials using conventional chemotherapy even if the biological and clinical features in elderly MM patients are identical to those of younger patients. 3 In the absence of any significant improvement after various conventional chemotherapy regimens, high-dose therapy with autologous stem cell transplantation (ASCT) has been extensively used in the last decade leading to higher complete remission (CR) rate with longer event-free (EFS) and overall survivals (OS). 4,5 Although the benefit from ASCT is mainly seen in a subgroup of patients with favourable initial characteristics who achieve CR post-ASCT, it is also of value in patients with resistant disease.…”
Section: Introductionmentioning
confidence: 99%